Developing Online Discipline-Based Art Education Courses for Adult Learners - Noiwangklang, Pisit; Rohitasuk, Sitthidham; Vijitsatitrat, Atipat (Thammasat Journal, 2026)
This study aimed to 1. investigate the development of an online curriculum grounded in discipline-based art education (Discipline-Based Art Education: DBAE) for adult learners, 2. design and implement an online curriculum that enables learners to develop art business plans, and 3. enhance instructional processes that support learners in creating such plans through online modules. The curriculum integrated DBAE principles with blended learning strategies and educational technology, particularly MOOCs, to support lifelong learning among adult learners who face time constraints. The research findings indicated high levels of learner satisfaction, particularly in course diversity, modernity, and user convenience (average satisfaction score = 4.57), with the overall system rated at 4.36. Learners were able to create art business plans that met assessment criteria. No significant differences were found between instructional formats (p = 0.579), suggesting curriculum consistency. These results support the value of an art-based, entrepreneurially focused online curriculum in promoting flexible, lifelong learning for adults in the digital era.